The aryl hydrocarbon receptor is associated with monocytic AML and innate immune resistance reversible with an AHR inhibitor - Saultz, Jennifer N.; Bottomly, Daniel; Burns, Faith; Byrd, Kaelan; Kosaka, Yoko; Alber, Bernhard; Chandra, Daniel; Kurtz, Stephen E.; Fan, Guang; Kaempf, Andy; Long, Nicola; Sanchez-Martin, Marta; et al. (Frontiers in Immunology, 2025)
BackgroundAcute myeloid leukemia (AML) is characterized by a complex interplay between genomic alterations, aberrant hematopoiesis, and immune evasion. The aryl hydrocarbon receptor (AHR) pathway is a critical player in this phenomenon determining the fate of stem cell differentiation as well as dictating immune cell development and function. Despite this critical connection, little is known about how AHR regulates the immune microenvironment in AML.MethodsWe performed a retrospective study examining the pre-treatment effect of immune cell numbers (T and NK cells) in the bone marrow and their impact on overall survival in AML patients undergoing 7+3 induction chemotherapy. Utilizing flow cytometry and both bulk and single-cell RNA sequencing of AML patient samples, we characterized the immune signature of blast cells and the influence of AHR on the immune microenvironment. Lastly, we performed functional studies to determine impact of pharmacological and genomic AHR inhibition on NK cell function.ResultsHigher bone marrow NK cell percentage in ND-AML correlated with poorer OS and expression of HLA-E on leukemic blasts. AHR upregulation was associated with HLA-E expression on blasts and an innate immune resistant signature defined by upregulation of key cytokine pathways, interferon gamma (IFN-g) pathway, and MHC class I/II as well as impaired NK cell profiles. High AHR expression in AML was associated with monocytic maturation and discrepant MHC class I/II profiles. Pre-treatment of blasts with an AHR inhibitor (AHRi) prior to NK cell killing assay downregulated key checkpoint molecules, including HLA-E, and key IFN-g signaling transcription factors (STAT1, IRF1) and led to enhanced NK cell killing among multiple FAB subsets in AML.ConclusionThe data support targeting the AHR pathway as a dual tumor intrinsic and immune targeting therapeutic strategy for AML, particularly in combination with NK cellular therapy.